BAid: smart hearing aid wristband / Siti Nur ‘Ain Abdul Rahman … [et al.] - Abdul Rahman, Siti Nur ‘Ain; Alias, Nur Elinawaty; Mohd Nasir, Nur Farah Najwa; Nik Mansor, Nik Nazifa Husna Putri; Zulkifli, Nurul Aina Najiha; Wei Loon, Koe (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This paper introduces a novel smart aid hearing wristband designed specifically for deaf individuals, aimed at enhancing communication accessibility and ease of interaction in daily life. The device incorporates innovative features such as a speaker button for sound detection and connection to companion apps, enabling real-time speech-to-text conversion displayed on the user's smartphone screen. Additionally, the wristband utilizes vibration alerts customized with registered names to efficiently capture the attention of the wearer during incoming calls. The practicality and usefulness of this device are emphasized, offering a comfortable and convenient solution for daily communication challenges faced by the deaf community. Simple instructions ensure easy adoption and seamless integration into the user's lifestyle, making it an indispensable tool for enhancing communication accessibility. With its potential for commercialization, this smart aid hearing wristband represents a promising opportunity for companies to address the needs of the deaf market while also contributing to social inclusivity and technological innovation.